Can Kidney Deceased Donation Systems Be Optimized? A Retrospective Assessment of a Country Performance - Domingos, M (2012)
BACKGROUND: The intensive requirement of organs for transplantation generates the need for higher rates of donation. METHODS: Using the national database of diagnosis-related groups for 2006, the global annual 2006 in-hospital mortality of 34 hospitals with organ-retrieval schemes was evaluated. Potential donors were estimated excluding patients aged <1 year or >70 years and presenting International Classification of Diseases, Ninth Revision codes that contraindicated organ donation. RESULTS: We identified 3838 potential donors (12.6% of in-hospital deaths); 46% came from eight hospitals, 80% came from the larger hospitals and 21% from intensive care units (ICU). In hospitals with a neurosurgical department, an office coordinator of procurement and transplantation (OCPT), a transplant centre and co-location of neurosurgical and transplant centre, we identified, respectively, 54, 30, 32 and 30% of all potential donors. The causes of death were 23% cerebrovascular disease, 3% cerebral tumour, 2.6% anoxic lesion and 2.5% head trauma. In the same period, there were 189 effective deceased kidney donors with traumatic diseases as the main cause of death. The mean conversion rate was 4.9% and was associated with demographical and hospital characteristics. Age of potential donors, existence of OCPT or transplant centre, ratio between ICU and hospital acute beds and mortality from labour accidents were predictors of being an effective donor. CONCLUSIONS: Health policies need to maximize the conversion of potential to effective donors and the performance of organ donation systems must be considered as an index of the quality of care.